Enhanced mechanical properties of 3 mol% Y2O3 stabilized tetragonal ZrO2 incorporating tourmaline particles. Issue 13 (September 2018) - Song, Yanjun; Zhu, Dongbin; Liang, Jinsheng; Zhang, Xiaoxu
Abstract: The current study reports on the improvement of mechanical properties of 3 mol% Y2 O3 stabilized tetragonal ZrO2 (3Y-TZP) by introduction of tourmaline through ball milling and subsequent densification by pressureless sintering at 800, 1200, 1300, 1400 °C. Findings demonstrate that no matter which sintering temperature the 3Y-TZP ceramic containing 2 wt% tourmaline reach a maximum value in flexural strength and fracture toughness as compared to other composite ceramics. As the tourmaline content is 2 wt% and the sintering temperature is 1300 °C, the flexural strength and fracture toughness of the composite ceramics are the highest, increases of 36.2% and 36.6% over plain 3Y-TZP ceramic respectively. The unique microstructure was systematically investigated through X-ray diffraction, scanning electron microscopy, energy dispersive spectrum, and flourier transform-infrared. The strengthening and toughening mechanism of tourmaline in 3Y-TZP ceramic were also discussed.